Conceptualising energy nationalism in the context of climate change: framework and review - Żuk, Piotr; Conversi, Daniele; Żuk, Paweł (Frontiers in Energy Research, 2024)
This article argues that the more energy policies are circumscribed within the borders of individual nation states, the more difficult it will be to implement the climate action on a global scale. The authors shed light on the relationship between nationalism and the simultaneous challenges of environmental protection, energy transition and climate change mitigation. Based on the review of various publications referring to nationalism in the context of energy policy and energy transition, the authors conceptualise this notion. Energy nationalism is defined here as any political decision, economic action